Pleasing the ghost - Creech, Sharon; Schuett, Stacey (New York, NY : HarperCollins, 1996)
Nine-year-old Dennis, whose uncle and father died within a year of one another, is visited by the ghost of his uncle, and together they settle some unfinished business.
Faculty.
Keywords: Ghosts -- Fiction; Uncles -- Fiction; Aunts -- Fiction; Communication -- Fiction